(1+1)-Dirac particle with position-dependent mass in complexified Lorentz scalar interactions: Effectively PT-symmetric - Mustafa, Omar; Mazharimousavi, Seyed Habib (SPRINGER/PLENUM PUBLISHERS, 2008)
The effect of the built-in supersymmetric quantum mechanical language on the spectrum of the (1 + 1)-Dirac equation, with position-dependent mass (PDM) and complexified Lorentz scalar interactions, is re-emphasized. The signature of the “quasi-parity” on the Dirac particles’ spectra is also studied. A Dirac particle with PDM and complexified scalar interactions of the form S(z) = S(x − ib) (an inversely linear plus linear, leading to a PT −symmetric oscillator model), and S(x) = Sr(x) + iSi(x) (a PT -symmetric Scarf II model) are considered. Moreover, a first-order intertwining differential operator and an η-weak-pseudo-Hermiticity generator are presented and a complexified PT -symmetric periodic-type model is used as an illustrative example.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Dirac Particle; Position-Dependent Mass; Complexified Lorentz Scalar Interactions